A LITERATURE REVIEW ON THE INTERPLAY OF GENERAL AND DENTAL DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The mucous membrane (MM) of the oral cavity and the dentoalveolar apparatus, along with the skin and eyes, can be involved in the pathological process in various somatic diseases. Changes in the mucous membranes of the oral cavity, periodontium and teeth may be a manifestation of the activity of a single systemic process, a consequence of the side effects of drug therapy, or may be due to a decrease in the quality of oral hygiene due to the patient’s serious condition. Awareness of therapists and dentists, correct and timely assessment of such changes and effective interdisciplinary interaction can help improve the success of diagnosis and treatment of both local manifestations and the underlying disease, as well as avoid a number of complications when performing dental procedures.